Genetic parameters and genome-wide association study for linear conformation traits, milking ease and temperament in Dairy Gir - Cunha, Samla Marques Freire (2020)
Conformation and handling traits can be used in the indirect selection to improve longevity, health, and welfare of dairy cattle. To optimize genetic gains for these traits it is necessary use statistical models that will best fit the phenotypic data and allow the understanding on how these traits respond to selection and their genetic association with milk yield. The knowledge about genetic variants that may be associated with these traits can also contribute to the selection process. The objective of this study was to determine how fixed and random effects should be included in the statistical models for conformation traits, milking ease, temperament, and 305-days cumulative milk yield for Dairy Gir cattle and estimate genetic and phenotypic parameters. Besides, aimed identify genes and quantitative trait loci (QTL) associated with udder conformation traits, milking ease, and temperament of the breed. The genotype and phenotype records used in this study was provided by Embrapa Dairy Cattle (Embrapa Gado de Leite). To identify the model that fitted the data better, four models were tested in one-trait analyses performed to estimate the variance components using the Average Information Restricted Maximum Likelihood (AIREML) within linear and threshold model. Akaike information criterion (AIC) and Bayesian information criterion (BIC) were used to identify which model fitted the data better. Two-trait analyses were performed using AIREML methodology to estimate genetic and phenotypic parameters for the studied traits. The weighted single-step genome-wide association study methodology was used to identify moving windows of 20 adjacent SNP that explained more than 1% of the total genetic variance. Candidate genes were annotated inside the identified widows using the ARS-UCD1.2 bovine genome assembly, and QTL annotation was performed using the UMD3.1 bovine genome assembly. Functional information and biological pathways were identified using the candidate genes. Linear models performed better than threshold models based on their AIC and BIC values. Among the linear models, the one that included only significant (p<0.05) fixed effects and contemporary group (CG) as random effect fitted better the phenotypic data, based on the AIC and BIC values. Heritability estimates for the studied traits ranged from 0.07 (0.01) to 0.50 (0.03). Heritability and repeatability estimates for continuous traits were higher when compared to heritability estimates from traits measured in categorical scale. The selection to increase rump length, rear udder width, udder depth, and teat diameter can contribute to increase the mean of milk yield due to genetic correlation estimates between them. The genomic association study identified important genes and relevant QTL for udder conformation and handling traits. Fore udder attachment was associated with three genomic windows (BTA 1, 21, and 28). Among the identified genes within these regions, the KLC1 and XRCC3 (BTA21) were found express in mammary gland tissue which make them candidates genes related to the studied trait. For rear udder width, one genetic window located on BTA1 was found explained more than 1% of the genetic variance. Genomic windows on BTA1, were identified for fore udder attachment and rear udder width overlapping. For both windows, the URB1 was found which can make it a candidate gene; however, little in know about its function. Five windows were located on BTA 5, 6, 9, 14, and 16 for udder depth. On BTA14, two candidate genes were identified (CYP7B1 and BHLHE22) and both genes were found related to mammary gland tissue. The CYP7B1 gene was related to onset the puberty, estrogenic functions, and reproductive organs and mammary gland development. For milking ease and temperament, two (BTA 5 and 19) and three (BTA 4, 18, and 29) windows was associated with the traits, respectively. One gene (CA10) was identified for milking ease within BTA 19 which is related with synapses function in the cerebrum and plays a role in secretory pathways. Two genes were identified for temperament located on BTA4 and BTA18 (TFEC and CDH11, respectively) and they are related with behavioral traits. Based on these results, the statistic model with the best fit for the phenotypic data included only statistically significant (p<0.05) fixed effects and CG as random effect. Heritability estimates showed that it is possibly change the studied traits through selection. The traits with the high response to selection will be stature, teat length, and navel length. The results obtained from the genomic association study can be helpful to understand the genetic structure of the udder conformation traits, milking ease, and temperament; specially, fore udder attachment, udder depth, milking ease, and temperament. All results found here are very important in the breed genetic development and can be applied in the Gir breeding program.